Contextual adaptation of digital wellbeing interventions for young people: insights from a project in Saudi Arabia - Aljuboori, Dahlia; Clary, Laura K.; Alomairah, Saud Abdulaziz; Colder Carras, Michelle; Saquib, Nazmus; Saquib, Juliann; Albeyahi, Fahad; Van Rooij, Antonius J.; Tuijnman, Anouk; Van der Rijst, Vincent G.; Kaufman, Michelle R.; Thrul, Johannes (Frontiers in Psychiatry, 2025)
In today’s world, the internet is seamlessly woven into every facet of our existence. This constant engagement with digital media has generated concerns about the negative effects of digital media use, especially among adolescents. These concerns have led to the development and testing of numerous digital wellbeing interventions that focus on adolescents’ digital media use. However, these interventions are lacking in the Middle East and North Africa, and specifically in Saudi Arabia, where digital media use is highly prevalent and frequent. Our research team is conducting a series of studies - literature reviews, stakeholder engagement work, and a nationwide survey of adolescent digital media use - to inform, develop, and ultimately test school-based digital wellbeing intervention for high school students in Saudi Arabia. The goal of this manuscript is to explain our process of informing and creating an intervention that builds on previously established, evidence-based approaches, and is also tailored to a particular context (e.g., Saudi Arabia). Moreover, we distill the lessons learned from each study and provide recommendations to assist others in developing tailored digital wellbeing interventions for contexts that have not been the focus of previous intervention development.